Pengembangan Briket Sekam Padi untuk Pemberdayaan Petani Desa Ogan Jaya, Lampung Utara - Hidayat, Rahmat; Saputra, Anggi; Fitria, Murni; Feladita, Niken (Jurnal Nusantara Mengabdi, 2025)
Purpose: This program aims to empower farmer groups to utilize rice husk waste into alternative fuel through simple briquette-making technology based on the circular economy concept. Methodology/approach: The program employed a participatory approach, involving local communities through several stages, including socialization, environmental education, and technical training on briquette production. The training covered rice husk carbonization, binder preparation, briquette molding, and drying processes. Evaluation was carried out through participant involvement observation, pre-test and post-test assessments, and product quality trials. Results/findings: The results show a significant increase in community knowledge, with over 39% improvement between pre-test and post-test scores. Participants, particularly farmer group members, showed high enthusiasm throughout the activities, and more than 75% successfully produced briquettes independently. A simple briquette press tool was also handed over to the community and proven to be functional and easy to operate. Conclusions: The program effectively enhanced community skills and awareness in renewable energy utilization. Simple technology can convert agricultural waste into economic value while supporting environmental sustainability. Limitations: The short implementation period restricted long-term mentoring and evaluation of sustainability. The number of participants was limited to 15 farmers, reducing generalizability. Moreover, no detailed economic or environmental assessments were conducted, so efficiency and emission impacts remain unquantified. Contribution: This program enhances community capacity in utilizing rice husk waste through simple briquette-making technology. It promotes renewable energy awareness, supports the circular economy, and strengthens collaboration between universities and farmer groups as a replicable model for rural energy innovation.